Impact of Magnetic Field on Magnetic States in Kagome Magnets - Tran, Thanh Mai; Tran, Minh Tien (Communications in Physics, 2022)
Impact of magnetic field on the magnetic states in kagome magnets is studied. The magnetic field is patterned in such a way that it can generally maintain the most prominent magnetic states in kagome magnets, such as the out-of-plane ferromagnetism and the in-plane antiferromagnetism. The tight-binding model with the spin-orbit coupling and the magnetic field on the kagome lattice is exactly solved. In both the out-of-plane ferromagnetic and the in-plane antiferromagnetic states the magnetic field opens a gap at half filling. In the out-of-plane ferromagnetic state both the half topological state, where only one spin component is topologically nontrivial, and the quantum spin anomalous Hall effect, where both spin components are topologically nontrivial, can be observed. The in-plane antiferromagnetic state may be insulating, but it is topologically trivial. The quantum anomalous Hall effect may also be observed in canted \(\sqrt{3} × \sqrt{3}\) antiferromagnetic state.